Reconstruction of the skullcap with PMMA prototyped implant after decompressive craniectomy. - C. Campolina, Ana; Maricevich, Pablo (Brazilian Journal of Implantology and Health Sciences, 2020)
INTRODUCTION: Decompressive craniectomy is indicated for the treatment of intracranial hypertension in cases of serious traumatic brain injury. This surgery results in a bizarre appearance, as if "part of the head" had been. After regression of cerebral edema and when the patient is in good clinical condition, the reconstruction of the skull is indicated. Reconstruction of the skull can be performed with autologous bone or with alloplastic materials. This study sought to present the experience of the author with skull reconstructions using custom PMMA prostheses. METHODS: In between 2014 and 2015, fourteen patients with previous (longer than 6 months) decompressive craniectomies were selected after Neurosurgery medical clearance and underwent skull reconstruction with customized PMMA prototyped prostheses. Signs and symptoms of syndrome of the trephined, computed tomography, and aesthetic appearance of the patients were analyzed preoperatively and at 6 months after reconstruction. RESULTS: All patients presented with improved symptomatology, aesthetic improvement and expansion of the brain after surgery. CONCLUSION: Reconstruction of the skull with customized prototyped PMMA prostheses improved the signs and symptoms and the aesthetic appearance in all 14 patients of this series. The use of prototypes to customize cranial prostheses facilitates the operative technique and enables patients to develop a nearly normal cranial contour.